A Mechanobullous Disease Of The New Born : Bart′s Syndrome - Jaiswal A K; Bhardwaj Mukta (Wolters Kluwer Medknow Publications, 1997)
A neonate with a unique congenital mechanobullous disorder (Bartâ€s syndrome) is described and compared with similar patterns from the literature. The blisters were sub epidermal, remitted within a few months and have not recurred on long- term follow â€" up. The relation of Bartâ€s syndrome to epidermolysis bullosa is unclear.